2008
DOI: 10.1091/mbc.e08-04-0362
|View full text |Cite
|
Sign up to set email alerts
|

Three Members of the LC8/DYNLL Family Are Required for Outer Arm Dynein Motor Function

Abstract: The highly conserved LC8/DYNLL family proteins were originally identified in axonemal dyneins and subsequently found to function in multiple enzyme systems. Genomic analysis uncovered a third member (LC10) of this protein class in Chlamydomonas. The LC10 protein is extracted from flagellar axonemes with 0.6 M NaCl and cofractionates with the outer dynein arm in sucrose density gradients. Furthermore, LC10 is specifically missing only from axonemes of those strains that fail to assemble outer dynein arms. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Strains and Media-C. reinhardtii mutants used in this study were oda12-1nit1 (a double mutant between oda12-1, which is a null mutant of the genes of two light chains LC2 and LC10 and lacks the entire outer arm, and the mutant nit1, which is deficient in nitrate reductase; this double mutant will be referred to as oda12) (10,11), oda11 (lacking the ␣ HC) (3), oda4-s7 (lacking the motor domain of the ␤ HC) (4), and oda2-t (lacking the motor domain of the ␥ HC) (5). The cells were grown in liquid Tris-acetate-phosphate medium with aeration on a 12 h of light/12 h of dark cycle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains and Media-C. reinhardtii mutants used in this study were oda12-1nit1 (a double mutant between oda12-1, which is a null mutant of the genes of two light chains LC2 and LC10 and lacks the entire outer arm, and the mutant nit1, which is deficient in nitrate reductase; this double mutant will be referred to as oda12) (10,11), oda11 (lacking the ␣ HC) (3), oda4-s7 (lacking the motor domain of the ␤ HC) (4), and oda2-t (lacking the motor domain of the ␥ HC) (5). The cells were grown in liquid Tris-acetate-phosphate medium with aeration on a 12 h of light/12 h of dark cycle.…”
Section: Methodsmentioning
confidence: 99%
“…This light chain is essential for proper OAD assembly, as evidenced by the fact that an LC2/LC10 null mutant, oda12, does not assemble functional OAD (10,26). Although oda12 lacks both LC2 and LC10, its motility defects can be rescued by transformation with a genomic fragment containing only the wild-type LC2 gene (10,11). We constructed a cDNA that encodes an LC2-BCCP fusion protein and used it to transform oda12.…”
Section: Production Of An Oad Complex Containing a Biotinylatedmentioning
confidence: 99%
“…In Chlamydomonas OAD, several LCs have been shown to bind the ICs and form an IC-LC complex [30; 31]. Three of them (LC6, LC8, and LC10) belong to the LC8/DYNLL family [31]. Our data raise the possibility that IC1 and IC2 can heterodimerize without the dimerization enhancers.…”
Section: Discussionmentioning
confidence: 76%
“…Of these, LC8 is known to be a dimerization enhancer [28]. In Chlamydo-monas OAD, several LCs have been shown to bind the ICs and form an IC-LC complex [29,30]. Three of them (LC6, LC8, and LC10) belong to the LC8/DYNLL family [30].…”
Section: Association Of Outer Arm Dynein Intermediate Chains In Vitromentioning
confidence: 99%
“…The oda6-r88 phenotype is likely due to the loss of either LC2 (a Tctex2-related protein) or LC9 (a Tctex1) as the LC6 protein, which appears to be Chlamydomonas -specific, is completely absent in oda13 which has wildtype beat frequency (DiBella et al , 2005). Although the oda12-1 strain which has a partial assembly defect and reduced beat frequency was originally described as lacking LC2 (Pazour et al , 1999) it was later found to also be a complete null for LC10 (Tanner et al , 2008) and thus to exhibit a synthetic phenotype due to the loss of both outer arm components.…”
Section: Key Dynein Regulatory Systemsmentioning
confidence: 99%